Graphene‐Oxide Mediated Chemodivergent Ring‐Opening of Cyclobutanols. Issue 11 (28th March 2023) - Brunetti, Andrea; Pintus, Angela; Lombardi, Lorenzo; Kovtun, Alessandro; Mascietti, Federico; Bruno, Francesco; Ravera, Enrico; Melucci, Manuela; Bertuzzi, Giulio; Bandini, Marco
Comprehensive Summary: The chemodivergent ring‐opening of cyclobutanols is described under the carbocatalytic assistance of graphene oxide (GO ). The protocol enables the synthesis of diversely functionalized dienes or indenes (26 examples) based on the amount of GO employed. Spectroscopic (XPS and ssNMR) as well as experimental investigations revealed a direct involvement of the π‐domains of GO in tuning the stability of carbocationic intermediates during the reaction. Abstract : Metal‐free σ‐C—C cleavage . The efficiency of graphene oxide in promoting the ring‐opening of cyclobutanols via C—C bond cleavage is documented in a chemodivergent manner. A range of functionalized indenes and dienes (26 examples) were selectively obtained in good yields (up to 89%) under mild conditions. Extensive XPS and ssNMR investigations supported the proposed mechanistic picture.